Relationships between plasma zinc and ferritin with nutritional status in thalassemic children - Luszy Arijanty; Sri Sudaryati Nasar; Bambang Madiyono; Djajadiman Gatot (Paediatrica Indonesiana, 2006)
Background Repeated blood transfusions in thalassemic chil-dren can lead to iron overload in the body. High ferritin level leadsto low plasma zinc status because of their competitive inhibition.Previous study found that there was a correlation between plasmazinc level and nutritional status.Objective To obtain plasma zinc level, to investigate the correla-tion between plasma zinc and ferritin, and the impact of plasmazinc on nutritional status in children with thallasemia.Methods A cross sectional study was conducted on 67 thalas-semic children. This study was performed at Thalassemia Center,Cipto Mangunkusumo Hospital, Jakarta, from 1 st until 31 st of March2005. The age of the patients ranged from 4 to 18 years, with fer-ritin levels more than 2000 ng/ml during the last 6 months or totaltransfusion more than 5 liters. The subjects were divided into 2groups, i.e. group 1 (4-10 years) and group 2 (>10-18 years). Di-etary intake was assessed by 3 day-dietary recall. The nutritionalstatus were judged by mid upper arm circumference (MUAC) forage and height for age (H/A). Venous blood was obtained to mea-sure plasma zinc and ferritin levels. Statistical analysis was doneby Student’s t-test (2-tailed) and linear regression analysis.Results We found that 42% subjects were well-nourished, 51%were undernourished, and 7% were severely malnourished. All sub-jects had low plasma zinc status 31.9 (SD 16.9) μg/dl. There was aweak negative correlation between plasma zinc and ferritin level (r= -0.282, P=0.021). Lower zinc intake was detected in 65 out of 67subjects.Conclusion All thalassemic children in our hospital had low plasmazinc level. There was a weak negative correlation between plasmazinc level and ferritin level. There was no significant correlationbetween plasma zinc status and nutritional status